2013
DOI: 10.1007/s11604-013-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of incidental F18-FDG breast uptake: a systematic review and meta-analysis

Abstract: This review aims to analyse the published data on the prevalence and clinical significance of breast incidental F18-FDG uptake detected by PET or PET/CT (BIU). A comprehensive computer literature search of the PubMed/MEDLINE, Scopus and Embase databases for studies on BIU published through July 2013 was performed. Pooled prevalence and malignancy risk of BIU were calculated. The literature search revealed 42 articles, and 17 were selected. One study was excluded because of data overlap but four additional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…In differentiating benign from malignant lesion SUV max values showed a low accuracy and a cut-off value couldn't be considered [6,7]. A recently published revision of the literature suggest that prevalence of hypermetabolic lesions in the breast is between 0.36 and 1.84% and overall risk of malignancy is between 18 and 100% [6]. This case report suggests that every breast uptake need further imaging in order to rule out malignancy.…”
Section: B16mentioning
confidence: 90%
See 3 more Smart Citations
“…In differentiating benign from malignant lesion SUV max values showed a low accuracy and a cut-off value couldn't be considered [6,7]. A recently published revision of the literature suggest that prevalence of hypermetabolic lesions in the breast is between 0.36 and 1.84% and overall risk of malignancy is between 18 and 100% [6]. This case report suggests that every breast uptake need further imaging in order to rule out malignancy.…”
Section: B16mentioning
confidence: 90%
“…Since screening procedure for breast cancer started a reduction of mortality was observed and an extension of lives despite the overdiagnosis still represents a problem. Despite screening procedure for breast cancer the data available in literature report a small number of incidental breast uptakes in patients studied with 18 F-FDG PET/CT for non-breast-related oncological reasons, which suggest that some lesions are still missed during traditional screening procedures [5][6][7][8]. In differentiating benign from malignant lesion SUV max values showed a low accuracy and a cut-off value couldn't be considered [6,7].…”
Section: B16mentioning
confidence: 99%
See 2 more Smart Citations
“…However, when an unexpected focus of FDG uptake is detected in the breast during an FDG examination performed for other reasons, it is necessary to explore it with conventional imaging and possible biopsy because of the high risk of malignancy [5]. In a meta-analysis of 13 studies, Bertagna et al [5] reviewed the breast incidental FDG uptake (BIU) detected by PET or PET/CT and demonstrated that the pooled prevalence of BIU on all scans was 0.4 % [95 % confidence interval (CI) 0.23-0.61 %], the pooled prevalence on scans on female patients only was 0.82 % (95 % CI 0.51-1.2 %), the pooled risk of malignancy of BIU when further analyzed was 48 % (95 % CI 38-58 %) and the pooled risk of malignancy of BIU with histological examination was 60 % (95 % CI 53-66 %).…”
Section: Introductionmentioning
confidence: 99%